Living photography and anamorphosis as equipment for public dying in a pandemic. Issue 2 (3rd July 2022) - Ohl, Jessy J.
ABSTRACT: This essay consists of a critical and creative encounter with WWI visual propagandist Arthur Mole's "living photography, " a technique to create images by configuring thousands of subjects to form silhouettes of culturally relevant symbols only discernable from an elevated vantage point. I argue that Mole's visual rhetoric offers important equipment for public dying, which in this case refers to rhetorical resources for managing collective mortality amidst the lethal concoction of pandemic, anti-Black racism, and war. As I theorize how living photography inventively encapsulates the enormity of multiple pandemics via anamorphosis, I make frequent departures between 1917–18 and 2019–21 by foregrounding Mole's most technically sophisticated image – a human assemblage resembling the Statue of Liberty taken at Camp Dodge in Des Moines, Iowa on August 23, 1918. Mole's rhetoric remains an aesthetically innovative, ethically perplexing, and historically neglected case that vivifies the opportunities and challenges of collectivist aesthetics to democratically address global cataclysm.